2002
DOI: 10.1002/gea.10021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the maritime Sites and Monuments Record with side‐scan sonar and diver surveys: A case study from Rathlin Island, Ireland

Abstract: Rathlin Island, off the north coast of Ireland, has a history of settlement and seafaring from the Late Mesolithic period to the present day. The maritime Sites and Monuments Record (SMR) for Rathlin indicates many wrecking incidents. In 1999, a reconnaissance side-scan sonar survey confirmed the presence of 46 targets of possible archaeological potential around Rathlin Island. Thirteen of these anomalies were positively identified as shipwrecks. Of the remaining 33 targets, nine were dived on in order to grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, a number of factors can influence the success of a search with side-scan sonar. Quinn et al [48] found that a geophysical survey, such as one with side scan sonar, provides a quick and effective survey method, although it is dependent on the experience of the operator, the navigation by the driver, and the quality of the image.…”
Section: Benefits Of Side Scan Sonarmentioning
confidence: 99%
“…However, a number of factors can influence the success of a search with side-scan sonar. Quinn et al [48] found that a geophysical survey, such as one with side scan sonar, provides a quick and effective survey method, although it is dependent on the experience of the operator, the navigation by the driver, and the quality of the image.…”
Section: Benefits Of Side Scan Sonarmentioning
confidence: 99%
“…The interpretation of sonar and magnetometer data for archaeological research was focused on the identification of Banomalies^ (Quinn et al 2002(Quinn et al , 2005.…”
Section: Geophysical Surveymentioning
confidence: 99%
“…Results from these and more recent marine geoarchaeological surveys suggest that images of large intact objects and artefact assemblage, such as upstanding wrecks, can be insonified with side-scan sonar and readily interpreted [2,4,9,10,18,25], but difficulties in imaging and interpreting smaller object types and scattered wreck material exist [17,19].…”
Section: Introductionmentioning
confidence: 96%
“…This approach is widely used in checking the veracity of conventional surveys undertaken in near-zero underwater visibility [18] and for monitoring changes in wreck structures and site development with reference to the natural environment [16]. It has also proved invaluable in making quick assessments of new sites about which there is little quantified information but, even then, it is possible to interpret appropriately-shaped natural phenomena as wreck-sites [19].…”
Section: Introductionmentioning
confidence: 99%